Cognitive performance is associated with gray matter decline in first-episode psychosis. (30th June 2017) - Dempster, Kara; Norman, Ross; Théberge, Jean; Densmore, Maria; Schaefer, Betsy; Williamson, Peter
Abstract: Progressive loss of gray matter has been demonstrated over the early course of schizophrenia. Identification of an association between cognition and gray matter may lead to development of early interventions directed at preserving gray matter volume and cognitive ability. The present study evaluated the association between gray matter using voxel-based morphometry (VBM) and cognitive testing in a sample of 16 patients with first-episode psychosis. A simple regression was applied to investigate the association between gray matter at baseline and 80 months and cognitive tests at baseline. Performance on the Wisconsin Card Sorting Task (WCST) at baseline was positively associated with gray matter volume in several brain regions. There was an association between decreased gray matter at baseline in the nucleus accumbens and Trails B errors. Performing worse on Trails B and making more WCST perseverative errors at baseline was associated with gray matter decline over 80 months in the right globus pallidus, left inferior parietal lobe, Brodmann's area (BA) 40, and left superior parietal lobule and BA 7 respectively. All significant findings were cluster corrected. The results support a relationship between aspects of cognitive impairment and gray matter abnormalities in first-episode psychosis. Highlights: Impairments in executive functioning characteristic of schizophrenia are associated with progressive gray matter volumetric differences evident over the early course of schizophrenia. Gray matter volume at initial presentation of psychosis was positively associated with performing worse on the WCST at baseline. Gray matter decline over 80 months was associated with impairments on the Trails B at baseline in the right globus pallidus, and left inferior lobule and Brodmann's Area 40. Gray matter decline over 80 months was associated with worse performance on the WCST at baseline in the left superior parietal lobule and Brodmann's Area 77. These results support a process of neurodegeneration and/or pruning in the early course of illness and highlight the importance of early intervention efforts during this critical time.